Evaluación de registros holter durante 19 horas en el contexto de la teoría de la probabilidad (2023)
method to help evaluate 21- hour holter recordings based on dynamic systems and the theory of probability was previously developed Aim: to evaluate the diagnostic value of this methodology in the analysis of 19 hr compared to conventional holter anal